DEVELOPMENT OF GROUP COUNSELING GUIDE WITH RELAXATION, SYSTEMATIC DESENSITIZATION, AND FLOODING TECHNIQUES TO REDUCE INTERACTION ANXIETY - Sari, Eva Kartika Wulan; Latifah, Leny (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2023)
This study aims to develop group counseling guidelines incorporating relaxation techniques, systematic desensitization, and flooding to alleviate anxiety in interactions among junior high school students. The research follows a developmental research model adapted to field conditions, encompassing six stages: (1) planning, (2) product development, (3) expert testing of guidance and counseling materials, media testing, (4) product revision, (5) user testing, and (6) finalization of the group guidance counseling product. The validation of this guide involved four validators, including two material experts, a media expert, and product users. Material expert testing yielded an average score of 3.5 (absolutely appropriate), while the media expert test resulted in an average score of 3.9 (absolutely appropriate), and the product user test obtained an average score of 3.3 (absolutely appropriate). Product revisions were made based on feedback from expert testers, ensuring that the guidebook is considered highly useful, easy to use, precise, interesting, and suitable for counselors to assist students in reducing anxiety during interpersonal interactions. It is important to note that this research is limited to user trials, and counselors are cautioned against implementing the guidelines without further recommendations.